The Mediating Effect of Innovation in the Relationship between Intellectual Capital and Institutional Performance - Fariz Fariz; Tutik Winarsih (Jurnal Ilmiah Manajemen Kesatuan, 2026)
In knowledge-intensive organizations like higher education institutions, the connection between intellectual capital and institutional performance has recently drawn significant academic attention. This study examines whether human, structural, and relational capital individually contribute to better institutional performance through innovation. With a sample of 242 academic staff and structural leaders from public and private universities, the study employed Partial Least Squares Structural Equation Modelling (PLS-SEM) using SmartPLS 4 software. According to the results, innovation is significantly and positively influenced by all three elements of intellectual capital. Furthermore, relational capital and innovation both exert significant direct effects on institutional performance. Innovation fully mediates the relationships between human capital and institutional performance, and between structural capital and institutional performance, while partially mediating the relationship between relational capital and institutional performance. This study concludes that human and structural capital do not significantly improve institutional performance without the intervening role of innovation, whereas relational capital contributes significantly to institutional performance both directly and through innovation. These findings extend the intellectual capital–innovation–performance framework beyond its conventional commercial origins into the higher education context, offering actionable insights for institutional leaders and policymakers seeking to leverage knowledge assets for sustainable performance improvement.